Effect of Adenine Sulphate with Giberellic Acid and Cytokinin on Indirect Organogenesis from Different Explants in Jatropha curcas L. - Kumari, Maya; Patade, Vikas Yadav; Arif, Mohommad; Ahmed, Zakwan (Indian Forester, 2013)
>Jatropha curcas L. is widely viewed as potential energy plant. Crop improvement in Jatropha through conventional means is difficult owing to its perennial nature, single flower bearing in a year and highly heterozygous nature because of open cross pollination. To improve this crop genetically, a simple, efficient, and reproducible method for plant regeneration through indirect organogenesis from leaf, cotyledon and petiole explants of J. curcaswas developed using Murashige and Skoog (MS) medium supplemented with different concentration of 6-Benzylaminopurine (BAP) along with adenine sulphate or auxins. Maximum callusing frequency of 93.3%, 96.7% and 83.3% with shoot bud induction of 96.7%, 41.7% and 38.7% and number of shoots 14.3, 14, 12.7 were obtained from cotyledon, leaf and petiole explants respectively. MS medium when supplemented with BAP along with adenine sulphate gave higher regeneration percentage (2-4 mg l-1 BAP+10 mg l-1 AS) and more number of shoots (14.3Â±1.1) compared to auxins (8.3Â±0.8). Elongation of shoots was achieved in MS supplemented with 2 mg l-1 BAP and 1.5 mg l-1 GA3 and rooting (93.3%) on MS medium with 0.5 mg l-1 IAA. Regenerated plantlets were successfully hardened (>80%) under culture room growth conditions.